Immunohistochemical differentiation of reactive from malignant mesothelium as a diagnostic aid in canine pericardial disease. (2nd April 2018) - Milne, E.; Martinez Pereira, Y.; Muir, C.; Scase, T.; Shaw, D. J.; McGregor, G.; Oldroyd, L.; Scurrell, E.; Martin, M.; Devine, C.; Hodgkiss‐Geere, H.
Abstract : Objectives: To develop a provisional immunohistochemistry panel for distinguishing reactive pericardium, atypical mesothelial proliferation and mesothelioma in dogs. Materials and Methods: Archived pericardial biopsies were subject to haematoxylin and eosin staining, immunohistochemistry for cytokeratin, vimentin, insulin‐like growth factor II mRNA‐binding protein 3, glucose transporter 1 and desmin. Samples were scored for intensity and number of cells stained. Results: Ten biopsies of reactive mesothelium, 17 of atypical mesothelial proliferation, 26 of mesothelioma and five of normal pericardium were identified on the basis of haematoxylin and eosin staining. Cytokeratin and vimentin were expressed in all biopsies, confirming mesothelial origin. Normal pericardial samples had the lowest scores for insulin‐like growth factor II mRNA‐binding protein 3, glucose transporter 1 and desmin. Mesothelioma and atypical proliferative samples were similar to each other, with higher scores for insulin‐like growth factor II mRNA‐binding protein 3 and glucose transporter 1 than the reactive samples. Desmin staining was variable. Insulin‐like growth factor II mRNA‐binding protein 3 was the best to distinguish between disease groups. Clinical Significance: An immunohistochemistry panel of cytokeratin, vimentin, insulin‐like growth factor II mRNA‐binding protein 3 and glucose transporter 1 could provide superior information compared with haematoxylin and eosin staining alone in the diagnosis of cases of mesothelial proliferation in canine pericardium, but further validation is warranted.